(untitled) (International Journal of Environmental Sciences, 2025)
This study explores socio-political cartography and spatial praxis being vindicated in Bani Basu’s Gandharvi: Life of a Musician and Moom and compares the state of transcendence in the two novels. By referring to Edward Soja’s spatial theory (Thirdspace: Journeys to Los Angeles and Other Real-and-Imagined Places 1996, 10), Northrop Frye’s archetypal critique (The Anatomy of Criticism: Four Essays 1957, 162) and Jürgen Habermas’ idea of the public sphere (Communication and the Evolution of Society 1979, 3) to make an intellectual discourse on the political, patriarchal, and traditional power structures in the society, which impede the capacity of a woman for free speech and self-formation. In Gandharvi, where music—once seen as holy, sacred, and redemptive—becomes desacralized within the tainted establishments of education and performance only to stunt and suppress the act of ‘transcendence and self-realization’. By employing Soja’s contention that space is politically charged, and indicative of underlying societal injustices in the urban sphere the study will also negotiate Moom and substantiate the standpoint the difficulties of achieving democratic ideals in a sharply divided modern world. It will be doubly intensified when it comes to a woman by highlighting the fundamental conflicts between the ideal of a communicative public sphere and the chaotic realities of lived space.